Viñas en la traza de Santiago del Nuevo Extremo y chacras colindantes (siglos XVI-XVII) - Muñoz Correa, Juan Guillermo (Revista de Historia Social y de las Mentalidades, 2011)
This article describes the vineyards that were esta blished in the southern rim of the valley of the Mapocho, both within the urban area, the city of Santiago del Nuevo Extremo properly so (in small plots and backyards), and in the wider suburban area, in the plots adjudicated by the first governors and the town council, bounded by the La Cañada canal, the Santa Lucía hill, in the area of Chuchunco, and in the upriver lands of Apoquindo, Vitacura and Ñuñoa. A detailed accou nt is provided of the owners, the sale practices, grants, mortgages, dowries and donations.
Keywords: family farms; Santiago del Nuevo Extremo; winemaking; colonial economic; vineyards